INDUSTRI KECIL DI NEGARA BERKEMBANG DALAM PUSARAN PASAR GLOBAL - Lasarus Jehamat * (Pendidikan Sosiologi FIS UNY, 2011)
Developmentalism Regime of new order placed economics as commander becoming starting point of all life aspect. The aim of this policy is to attainment of growth of the economics which at the farthest. All of the production activity later; then reduced just for attainment of economic goals. Activity of such production in this context is big industry. Its clear rationalization, all of the owner of capital inculcate its capital at various invesment type which likeliest give advantage more is passing of mechanism capital accumulate. Agriculture clearly not become choice because assumed less or do not give advantage to capitalist clan. Small and middle enterprise also less of peeped because it don’t give contribution to heaping of capital. Enableness to small and middle enterprise forwards have to pay attention six step namely exacerbating of vision and goals of small and middle enterprise, repair of good infrastructure of software and also is hardware, arrangement of beneficial tariff of small and middle enterprise, intoducing social protection, support meassurement, and training and education. Kata Kunci : Industri, Globalisasi, Kesejahteraan